(untitled) (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
The purpose of this researcher is to describe and analyze the planning, implementation and evaluation of teachers in the use of leter puzzles to foster reading interest of grade I students at MIS Darul Falah Sungai Nyirih, Jawai District for the 2023-2024 Academic Year. This study uses a qualitative approach with a type of phenomenological research. The data collection techniques in this study used observation, interview and documentation techniques. The data analysis techniques used are data reduction, data presentation, and conclusion drawn. The data validity check technique uses source triangulation, technique triangulation, and member check. The results of this study show that: (1) the appearance of leter puzzles to foster interest in reading is in the form of a game of arranging random leters into meaningful words or phrases. The level of difficulty is adjusted to the ability of each student. The game content uses puzzle boards, vocabulary books, and whiteboards. (2) the use of leter puzzles for students in grade I is (a) preparation; (b) random puzzles; (c) compiling puzzles; (d) forming paterns; (e) Continue to try and reflect. (3) Students’ participation in the use of leter puzzles is that students generally listen to the teacher’s explanations during learning, with varying levels of atention. Some students dare to ask the teacher about the material that is not clear, but there are also those who are still embarrassed. Students are actively involved using puzzles, which help develop various skills such as problem-solving, fine motor skills, and cooperation.